2021
DOI: 10.31351/vol30iss1pp154-162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Patient Safety Culture in Iraqi Community Pharmacies

Abstract: Patient safety is the main issue in health care organization, the Agency for Healthcare Research and Quality defines it as, “freedom from accidental or preventable injuries produced by medical care. Thus, practices or interventions that improve patient safety are those that reduce the occurrence of preventable adverse events”. The purpose of this study was to evaluate Iraqi pharmacist perception about the culture of patient safety. As well as estimate whether safety is a principal issue in their pharmaceutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Five studies [14][15][16]18,22 were conducted on pharmacists, whereas 6 studies (8 surveys) 17,[19][20][21]23,24 were carried out on all pharmacy staff members such as pharmacists, technicians, clerks, and pharmacy students on apprenticeship. Two studies (3 surveys) 17,18 originated from the United States, and the remainder were distributed as follows: Malaysia, 14 Kuwait, 15 United Arab Emirates, 16 Ethiopia, 19 Saudi Arabia, 20 Qatar, 21 Iraq, 22 Jordan, 23 and Singapore. 24 Eleven studies had response rates between 24.0% and 99.2%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies [14][15][16]18,22 were conducted on pharmacists, whereas 6 studies (8 surveys) 17,[19][20][21]23,24 were carried out on all pharmacy staff members such as pharmacists, technicians, clerks, and pharmacy students on apprenticeship. Two studies (3 surveys) 17,18 originated from the United States, and the remainder were distributed as follows: Malaysia, 14 Kuwait, 15 United Arab Emirates, 16 Ethiopia, 19 Saudi Arabia, 20 Qatar, 21 Iraq, 22 Jordan, 23 and Singapore. 24 Eleven studies had response rates between 24.0% and 99.2%.…”
Section: Resultsmentioning
confidence: 99%
“…For additional analysis, 7 studies had performed comparative analysis and 2 studies 18,20 had performed multivariable logistic regression analysis. Among the 7 studies reporting comparative analysis, 5 studies compared PRRs according to the years of pharmacy practice, 14–16,21,22 and senior respondents showed a trend of higher PRRs for “teamwork,” “staff training and skills,” “staffing and work pressure,” “response to mistakes,” and “organizational learning–continuous improvement.” Specifically, senior staff members showed more positive responses to “staff work together as an effective team,” “technicians in this pharmacy receive the training they need to do their jobs,” “staff ideas and suggestions are valued in this pharmacy,” “we have enough staff to handle the workload,” and “when the same mistake keeps happening, we change the way we do things” items in more than 2 studies 14–16,19,21–23 . Studies from Kuwait, 15 Saudi Arabia, 20 and Qatar 21 categorized participants according to working hours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, community pharmacies have continuously attempted to improve the quality of health and pharmaceutical care services provided to patients, focusing on optimizing patient safety and decreasing unintended mistakes during healthcare delivery. Before the COVID-19 pandemic, several studies assessed patient safety culture in community pharmacy settings both internationally and regionally [ 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Previous research has identified organizational breakdown, insufficient staffing, increased production pressures, and provider fatigue as factors contributing to poor patient safety [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%